Pembangunan Sumber Daya Manusia di Wilayah APEC (Kajian Kesiapan Indonesia dalam Era Perdagangan Bebas) - Oke Setiarso; Nurul Anwar (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2006)
Theme of this research is around the ability of human resource development to Asia Pacific countries. Main problems on this research are how the comparison of human development among the countries and what variables that influence it.The economic, demographic, public health and education term have significant impact to human developing index in APEC area. Gross Domestic Product per capita, access to proper water, and expenditure of education have positive impact to HDI. Otherwise, total populations, population with HIV/AIDS, female life expectancy of birth, and inflation factor have negative impact to HDI.According to this research, first, the education sector has high contribution to the capacity of human development. Government should allocate more budgets spending to the sector. Second, highly infant mortality and low of female life expectancy of birth show that public health aspect no being measure of the success of human development target. Developing of this sector must be main priority. Third, government has to implement sustainability development process that use environmental sight. It is relevant to the efforts of giving public service, especially well sanitation and sufficient of purification water to all Indonesian civil.Keywords: human development, inflantion, female life expectancy